Les rebuts de la société de marché : toxicomanes, psychopathes, sans-abri dans les prisons de l’Amérique - Loïc Wacquant (Amnis)
Drugs addicts, the mentally ill, the homeless: the insufficiency and ineptness of social and medical services in the United States ensures that these three categories find themselves behind bars in ever larger numbers over time, as the prison is turned into a dumping ground for the human waste of a society more and more subordinated to the dictates of the market. Their fate thus offers a tragic experimental verification to the hypothesis of a causal and functional link between the withering away of the social state and the prosperity of the penal state.